Kajian Ikonografi pada Gedung Marabunta di Semarang - Sudarmono, Lois Debora (Intra, 2014)
Marabunta building is the public commercial building that located at 23 Cendrawasih, Semarang. This building was the former of StadSchouwburg opera building for the Europeans in the colonial era. StadSchouwburg building then went through a reconstruction process due to collapse, as a result of age and environmental causes. This new building was later named Marabunta building. The use of some interior elements at the hall area from StadSchouwburgâs interior elements origin gave the impression of an European style. Whereas the faÃ§ade design of this building is a new design that adapts to the surrounding style.The architectural and interior form of Marabunta building generated a meaning that interesting to assess. It was produced as the result of unification from the colonial style with the local cultures and historical aspect. This research uses the iconography study method proposedÂ  by Panofsky which aims to reveal the meaning in an object through a set of descriptional stages that consist of pre-iconography description and analysis of iconography, in which all of the stages are inter-connected. The stage of pre-iconography as the first step aims to acquire the prime/ natural meaning (textual meaning). Meanwhile, the stage of iconography analysis as the next inter-connected step aims to abtain the secondary/ conventional meaning (contextual meaning).The prime meaning that discovered in the stage of pre-iconography shows that the architectural and interior form of Marabunta building has similarities to the Indo â European Colonial building style with dominancy of Renaissance and other styles. In the stage of iconography, resulted the secondary meaning that reveals ornamental arrangement at the facade and interior building contains nationalism value that merged with the symbol of colonialism authorization. It makes the interpretation meaning of building as a freedom/ independence.Â